2005
DOI: 10.1051/gse:2004030
|View full text |Cite
|
Sign up to set email alerts
|

A presentation of the differences between the sheep and goat genetic maps

Abstract: -The current autosomal version (4.2) of the sheep genetic map comprises 1175 loci and spans ∼3540 cM. This corresponds to almost complete coverage of the sheep genome. Each chromosome is represented by a single linkage group, with the largest gap between adjacent loci being 19.8 cM. In contrast the 1998 goat genetic map (the most recently published) is much less well developed spanning 2737 cM and comprising only 307 loci. Only one of the goat chromosomes appears to have complete coverage (chromosome 27), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Overall, then, this marsupial species has the shortest recombinational map, and by inference the lowest recombination rate, yet described for any vertebrate; and, unlike other vertebrates, M. domestica females have much less recombination than males over most of the genome, a situation also observed in the linkage map of the distantly related model kangaroo species, M. eugenii, but in no other vertebrate for which extensive mapping data are available. (Potential exceptions reported in sheep (Maddox 2005) and Japanese flounder (Coimbra et al 2003) remain provisional. In sheep, peculiarities of the sex ratio of the mapping panel may have artificially expanded the estimate of male map length (Maddox et al 2001, p 1285, andpersonal communication), while in flounder the genetically unusual cross and substantially incomplete map of the single male parent suggest that the observed level of heterochiasmy may not be representative of the overall genome or the species in general.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Overall, then, this marsupial species has the shortest recombinational map, and by inference the lowest recombination rate, yet described for any vertebrate; and, unlike other vertebrates, M. domestica females have much less recombination than males over most of the genome, a situation also observed in the linkage map of the distantly related model kangaroo species, M. eugenii, but in no other vertebrate for which extensive mapping data are available. (Potential exceptions reported in sheep (Maddox 2005) and Japanese flounder (Coimbra et al 2003) remain provisional. In sheep, peculiarities of the sex ratio of the mapping panel may have artificially expanded the estimate of male map length (Maddox et al 2001, p 1285, andpersonal communication), while in flounder the genetically unusual cross and substantially incomplete map of the single male parent suggest that the observed level of heterochiasmy may not be representative of the overall genome or the species in general.…”
Section: Discussionmentioning
confidence: 89%
“…Eutherian linkage maps, for example, range from õ1400 centiMorgans (cM) in laboratory mice (Rhodes et al 1998) to more than 3500 cM in sheep (Maddox 2005) and humans (Kong et al 2004). The Ffirst-generation_ M. domestica sexaveraged linkage map, comprising 80 loci distributed among eight autosomal linkage groups, is only 633 cM long, excluding three unmapped X-linked loci (Samollow et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Several reports of linkage between genes and QTL with wool production traits are available for sheep (Parsons et al, 1994;Rogers et al, 1994;Allain et al, 1998Allain et al, , 2006Beh et al, 2001;Ponz et al, 2001;Purvis and Franklin, 2005;Bidinost et al, 2008). Because of the homology between sheep and goat maps (Crawford et al, 1995;Maddox, 2005), putative QTL affecting fleece traits found in the Angora goat on CHI1, CHI5 and CHI19 could be related to the keratin-associated protein (KAP) and keratin (KRT) gene family as pointed out by McLaren et al (1997). In sheep, on chromosome 1 (OAR1), OAR3 and OAR11 several high glycine-tyrosine keratin-associated proteins (KAP6.1, KAP7, KAP8, KAP1 and KAP3) and keratin genes (KRT1, KRT2, KRT2.13 and KRT2.10) were mapped by McLaren et al (1997).…”
Section: Discussionmentioning
confidence: 99%
“…A Bonferroni correction (derivative-free restricted maximum likelihood, DFREML) was used to analyze the relationship between GH gene and litter size with animal models (Meyer and Kirkpatrick, 2005). Pedigrees of base population animals were traced back three (Matou) or four (Boer) generations, in order to create the numerator relationship matrix.…”
Section: Methodsmentioning
confidence: 99%